Adsorption of heavy metal ions and epoxidation catalysis using a new polyhedral oligomeric silsesquioxane - Soares, Isaac V. [UNESP]; Vieira, Eduardo G. [UNESP]; Filho, Newton L.D. [UNESP]; Bastos, Andréa C. [UNESP]; da Silva, Niléia C. [UNESP]; Garcia, Edemir F. [UNESP]; Lima, Lucélia Julia A. (Elsevier, 2013)
The objective of this research was the preparation of a silsesquioxane functionalized with eight chloropropyl chains (T8-PrCl) and of a new derivative functionalized with a pendant linear chain (2-amino-1,3,4-thiadiazole - ATD; T8-Pr-ATD). The two nanostructured materials were characterized by 13C and 29Si NMR, FTIR and elemental analysis. The new nanostructured material, octakis[3-(2-amino-1,3,4-thiadiazole)propyl] octasilsesquioxane (T8-Pr-ATD), was tested as a ligand for transition-metal ions with a special attention to adsorption isotherms. The adsorption was performed using a batchwise process and the organofunctionalized surface showed the ability to adsorb the metal ions Cu (II), Co (II), and Ni (II) from water and ethanol. The adsorption isotherms were fitted by Langmuir, Freundlich, Temkin and Dubinin-Radushkevich (D-R) model. The kinetics of adsorption of metals were performed using three models such as pseudo-first order, pseudo-second order and Elovich. The Langmuir and Elovich models were the most appropriate to describe the adsorption and kinetic data, respectively. Furthermore, the T8-Pr-ATD was successfully applied to the analysis of environmental samples (river and sea water). Subsequently, a new nanomaterial was prepared by functionalization of the T8-Pr-ATD with a Mo (II) organometallic complex (T8-Pr-ATD-Mo). Only a few works in the literature have reported this type of substitution, and none dealt with ATD and Mo (II) complexes. The new Mo-silsesquioxane organometallic nanomaterial was tested as precursor in the epoxidation of cyclooctene and styrene. © 2012 Elsevier B.V.
Keywords: Adsorption; Catalysis; Functionalization; Preconcentration; Silsesquioxane; Batch-wise process; Cyclooctene; Dubinin-Radushkevich; Environmental sample; Freundlich; FTIR; Functionalizations; Functionalized; Kinetic data; Langmuirs; Linear chain; Nanomaterial; Octasilsesquioxane; Organofunctionalized; Organometallic complex; Polyhedral oligomeric silsesquioxanes; Pre-concentration; Pseudo second order; Silsesquioxanes; Three models; Adsorption isotherms; Ethanol; Heavy metals; Metal ions; Nanostructured materials; Nuclear magnetic resonance spectroscopy; Oligomers; Organometallics; Styrene; Transition metals; Molybdenum compounds